Two remarkable species of Phoradendron (Viscaceae) from the Oaxacan Mixteca (México), one new and the other supplemented - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2011)
Phoradendron perredactum, a miniature leafless and practically acaulescent stem parasite of Bursera discolor, is described as new and illustrated. Two types of individuals were observed: the more common branched ones, less than 1 cm long with a prevalence of female flowers, and the scarcer usually solitary ones to 3 cm long, with a prevalence of male flowers. The description of P. olae Kuijt is complemented with information concerning male plants and hosts. Both plants occur sympatrically in the District of Huajuapan de León in northwestern Oaxaca, Mexico.